Herbal product labels: do they guide rational or irrational use? - Adriany Barreto de Souza; Raimundo Fernandes Bento Filho; Milena Rezende Brito; Bruno de Paula Lima; Mayara Amoras Teles Fujishima; Carolina Miranda de Sousa Lima (São Paulo State University (UNESP), 2022)
Objective: The purpose of this study was to analyze the primary and secondary labels of plantbased medicines. Method: This research has a cross-sectional and descriptive. The procedure consisted of analyzing 100 labels of medicinal plant-based products used by elderly people from (in) Macapá-AP, in 2017. A script was prepared to verify their adequacy to health standards based on the Brazilian legislation (commercial name, botanical nomenclature, active ingredients, concentration, route of administration, age-restricted use, quantity and pharmaceutical form, preservation care, company name, CNPJ - Brazils's companies registration number, composition, SAC, expiration date, manufacture and batch), descriptive analysis of the data was performed (protocol number 38400314.9.0000.0003). Results: Only 4% of the products completely met the analyzed criteria. One of the main problems observed was the absence of a uniform standard of presentation of information on the packaging. About 7% of these products did not present any information besides the popular name of the medicinal plant used, 37% of the packages (or labels) contain statements and images that induce self-medication, errors in use, or references to "natural medicine", besides, transmitting the idea that the product has superior properties to drugs on the market. Conclusions: The results obtained suggest that the packaging of medicinal plant-based products induces the irrational use of medicines due to the lack of adequate information, as well as the presence of inadequate makenting strategies, in accordance with current national legislation.